2020
DOI: 10.1029/2020ja028221
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Plasma Waves Observed Upstream From Mars

Abstract: We describe a new method to analyze the properties of plasma waves and apply it to observations made upstream from Mars by the Mars Atmosphere and Volatile EvolutioN (MAVEN) mission. The slow measurement cadence of most charged particle instrumentation has limited the application of analysis techniques based on correlations between particle and magnetic field measurements. We show that we can extend the frequency range of applicability for these techniques, for a subset of waves that remain nearly coherent ove… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
20
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 74 publications
(135 reference statements)
8
20
0
Order By: Relevance
“…This trend is consistent with the result reported by Halekas et al. (2020) based on MAVEN observations. In contrast, Figure 7b shows the HR amplitude curves do not necessarily decrease with larger altitudes from Mars.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…This trend is consistent with the result reported by Halekas et al. (2020) based on MAVEN observations. In contrast, Figure 7b shows the HR amplitude curves do not necessarily decrease with larger altitudes from Mars.…”
Section: Discussionsupporting
confidence: 94%
“…PCWs are additionally observed for slower SW speeds (v SW < 400 km s −1 ), with a decreasing trend in occurrence rate for faster speeds. This is consistently seen for all HR groups and the entire span of available MAVEN data, confirming the results from Halekas et al (2020) between September and November 2018. Although this trend disagrees with linear wave growth theory (Gary et al, 1986), Delva et al (2015) also reported a similar case for PCWs near Venus from the Venus Express mission.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…In particular, newborn planetary protons (H + ) and oxygen ions (O + ) are picked up at these locations and in the Martian magnetosheath by the magnetized SW, as reported by Barabash et al (1991), Curry et al (2015), Dubinin et al (2006), Rahmati et al (2015, 2017), Yamauchi et al (2015), and Dong et al (2015). In addition to contributing to planetary escape, such picked‐up ions are responsible, among other outcomes, for the presence of different plasma instabilities (e.g., Andrés et al, 2020; Bertucci et al, 2013; Brain et al, 2002; Halekas et al, 2020; Liu et al, 2020; Mazelle et al, 2004; Romanelli et al, 2013, 2016; Ruhunusiri et al, 2015, 2016; Russell et al, 1990).…”
Section: Introductionmentioning
confidence: 99%